A Review on Ayurvedic Perspective of PCOS (International Journal of Ayurveda and Pharma Research, 2022)
Polycystic Ovarian Syndrome (PCOS) is one of the most common metabolic and reproductive disorders among women of reproductive age. It is characterized clinically as a combination of ovulatory dysfunction, hyper androgenic state and abnormal ovarian morphology. Women with PCOS are at increased risk of presenting with menstrual irregularities, hirsutism, obesity, insulin resistance, impaired glucose tolerance, Type 2 Diabetes mellitus, dyslipidemia and cardiovascular problems. PCOS being a syndrome cannot be correlated with any particular disease in Ayurveda. Hence for the better comprehension of this disease in terms with Ayurveda, the diseases mentioned in Ayurveda classics manifesting with signs and symptoms of PCOS have been studied in detail in relation with Nidana, Dosha, Srotas involved and their management. Diseases like Vandhya, Arajaska, Nashtarthava, Arthavakshaya and Pushpagni jathaharini shows resemblance in signs and symptoms and to some extend these can be related with PCOS